2021
DOI: 10.1186/s12866-021-02216-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of rhizosphere fungi on the chemical composition of fruits of the medicinal plant Cinnamomum migao endemic to southwestern China

Abstract: Background This study examined how rhizosphere fungi influence the accumulation of chemical components in fruits of a small population species of Cinnamomum migao. Results Ascomycota and Basidiomycota were dominant in the rhizosphere fungal community of C. migao. Pestalotiopsis and Gibellulopsis were associated with α-Terpineol and sabinene content, and Gibellulopsis was associated with crude fat and carbohydrate content. There were significant dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 75 publications
0
10
0
Order By: Relevance
“…Oleum Cinnamomi is the essential oil obtained from Fructus Cinnamomi , which is the dry and ripe fruit of Cinnamomum migao , a large evergreen of the Lauraceae family [ 37 ]. C. migao is only distributed in the dry and hot valleys of the Karma-Fenglin Mountain region.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Oleum Cinnamomi is the essential oil obtained from Fructus Cinnamomi , which is the dry and ripe fruit of Cinnamomum migao , a large evergreen of the Lauraceae family [ 37 ]. C. migao is only distributed in the dry and hot valleys of the Karma-Fenglin Mountain region.…”
Section: Resultsmentioning
confidence: 99%
“…Fungal groups stimulate the plant body to produce secondary metabolites, which are often the medically active ingredients of medicinal plants. According to a report, sabinene, the secondary metabolites of saprophytic fungi, can reflect the quality of C. migao in different regions [ 37 ]. In this study, the content of quality markers in Luodian samples was much higher than those in other origins.…”
Section: Resultsmentioning
confidence: 99%
“…Among them, Ascomycota had the highest relative abundance in sapling (81.20%), followed by mature (72.08%), and the lowest in overripe (38.74%), Basidiomycota had the highest relative abundance in overripe (57.25%), and the relative abundance in other periods was low (range 1.41%∼2.69%). Many studies have shown that Ascomycota and Basidiomycota were the dominant fungi in plant rhizosphere ( Chen et al, 2021 ). For example, in the rhizosphere of Picea asperata ( Liu et al, 2021 ), Castanopsis hystrix and Pinus massoniana ( Wang et al, 2021a ; Wang et al, 2021b ), the relative abundance of both fungi were higher than other fungi.…”
Section: Discussionmentioning
confidence: 99%
“…Glomus is recognized as a dominant AMF genus in the Karst regions of Southwest China [ 25 ]. Furthermore, previous research has confirmed that C. migao can co-exist with some AM fungi [ 26 , 27 ], and recently a study has analyzed the effects of AMF on C. migao drought tolerance under water deficit conditions in Karst soils by assessing inoculated seedlings [ 28 ]. However, none has explored the effects of different AMF inoculation methods or synergistic interaction between AMF species and inoculation methods on C. migao performance.…”
Section: Introductionmentioning
confidence: 99%